FKBP4 promotes glycolysis and hepatocellular carcinoma progression via p53/HK2 axis - Zhenzhen Zeng; Shasha Xu; Ruihua Wang; Xingmin Han (Scientific Reports)
Abstract FKBP4, a member of the FK506-binding protein (FKBP) family, is a promising target for a variety of disorders, including cancer. However, its underlying molecular mechanism and potential function in hepatocellular carcinoma (HCC) are largely elusive. Therefore, we aimed to investigate the expression status, functional implications and underlying mechanisms of FKBP4 in HCC. Our bioinformatics analysis of TCGA LIHC datasets, ICGC LIRI-JP datasets and GEO datasets results showed FKBP4 was upregulated in HCC tissues. We also confirmed the elevated FKBP4 in clinical HCC samples. Additionally, quantitative RT-PCR results revealed FKBP4 was highly expressed in all five tested HCC cell lines. We also observed a correlation between elevated FKBP4 expression and poor prognosis in HCC patients. Loss of FKBP4 can inhibit the proliferation and migration in HCC cells. Furthermore, we found that silencing FKBP4 suppressed glucose uptake, lactic acid production and 18F-FDG uptake compared with the control group. Mechanistically, our funding indicated that FKBP4 participates in glycolysis through p53 mediated HK2 signaling pathway, specially, FKBP4 knockdown promotes the expression and stability of p53 protein rather than affecting the transcription level. Finally, rescue experiments revealed that simultaneous knockdown of both FKBP4 and p53 partially reversed the inhibitory effects on HK2 protein levels and 18F-FDG uptake. Our study elucidates a novel role of FKBP4 in promoting HCC development and glycolysis by modulating the p53/HK2 signaling pathway. Given the critical role of aerobic glycolysis in the progression of HCC, targeting FKBP4 may offer a new therapeutic strategy for treating this malignancy.